Effects of Sound Praying on Stress and Respiration Rate of the First-Year Students, Faculty of Science - คคนานต์ดำรง, พรทิพย์; ปัทมโรจน์, อรุณรัตน์; มีอาจ , ฉัตรภรณ์; ชุ่มบัวทอง, อัญชลี; น้อยนารถ, ชัยยา; วณิชย์กุล, ณัฏฐ์พัชร์ (Journal of Health Science of Thailand, 2020)
The objective of this study was to examine the effect of sound praying on stress and respiratory rate. It was conducted with quasi-experimental research design, and the study samples were 40 first-year students of Faculty of science and Technology, Huachiew Chalermprakiet University, Thailand. They were divided into 2 groups: experimental group (20 students) and control group (20 students). The experimental group performed sound praying 3 times a week, 10 times in total and the duration of each praying was 15 minutes. The control group did not pray. The study tools were Suanprung Stress Test (20, SPST - 20) and a record form for respiratory rate. Data were analyzed by using descriptive statistics and t-test to compare the differences between the experimental group and the control. It was found that the mean stress score of the control group was higher than that of the experimental group (p=0.001), and the mean respiration rate of the control group was also significantly higher than that of the experimental group (p<0.001). While comparing the differences between the groups before and after the experiment with paired t-test, the average stress score before and after prayer was significant different (p<0.001). Likewise, the average respiration rates before and after prayer were also significant different (p<0.001). Therefore the sound praying was effective in reducing stress levels and respiratory rate among first year students of Faculty of Science and Technology, Huachiew Chalermprakiet University.